Enhancing truth discovery in document context finding using NER – based veracity evaluator framework - Azman, Siti Nuradilah; Ishak, Iskandar; Mohd Sharef, Nurfadhlina; Sidi, Fatimah; Affendey, Lilly Suriani (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Data veracity in one of the characteristic in 5V’s of Big Data. In which data veracity is refer to trustworthiness and consistency. There were several existing research on veracity that has been conducted since the last few years. However, the problem with existing research is, the context of the data used is unknown. The main objective of this research is to identify the context of a document which will further to be used in constructing the Veracity Evaluator Framework.